A comparative study between open lichtenstein mesh repair and laparoscopic totally extra peritoneal repair of inguinal hernia - Pooraneson, Karthik; N., Chandrashekar; Ranjan, Ved Prakash; S., Yamuna V. (International Surgery Journal, 2018)
Background: The study was conducted to compare and assess the duration of procedure, complications encountered, post-operative pain and recovery, duration of hospital stay, and time taken in resumption to work between two techniques of open Lichtenstein mesh repair (OLMR) and Totally extra peritoneal (TEP) repair in the low resource settings. Methods: A cross sectional comparative study was conducted among 50 male patients admitted for surgical repair of hernia. After considering the inclusion and exclusion criteria, the subjects were randomly assigned to the groups of OLMR and TEP and were assessed for pain in the post-operative period was rated using a Visual Analogue Scale. Total duration of the procedure, complications, duration of hospital stay, and time taken in resumption to work were elicited between two techniques. A p-value of <0.05 was taken as statistically significant. Results: The mean duration of surgery among the study participants in TEP (49.60+3.62 mins) group was significantly higher compared to OLMR (45.96+4.63 mins) group (p=0.003). The median of post-operative pain scores in TEP group was significantly lower compared to OLMR group. The mean duration of post-operative recovery time (3.08+0.4 days), for resumption to work (5.08+0.28 days) among the study participants in TEP group was significantly lower compared to OLMR (5.00+0.00 days), (10.08+0.76 days) (p<0.001) respectively. The complications were significantly higher among the OLMR group (100.0%) compared to the TEP group (p<0.05). Conclusions: Though the procedure of TEP repair for inguinal hernia takes a little longer time and complications of general anaesthesia cannot be ruled out, it is a better procedure compared to open type.